Can leader self-sacrificial behavior inhibit unethical pro-family behavior? A personal identification perspective - Hou, Changchang; Cheng, Ken; He, Jiaying; Hu, Panpan; Lin, Yinghui (Frontiers in Psychology, 2023)
As a kind of deviant and unethical behavior in the workplace, unethical pro-family behavior (UPFB) has recently received increased attention. Yet, the question of how to reduce UPFB remains less well understood. From the personal identification perspective, we hypothesize that leader self-sacrificial behavior (LSSB) inhibits employees’ UPFB through the mediation of identification with the leader. We further argue that employees’ perceived insider status enhances this hypothesized relationship. Our analysis of two-wave data collected from 236 Chinese employees indicated that identification with the leader partially mediated the negative relationship between LSSB and UPFB. Moreover, the effect of LSSB on identification with the leader and the aforementioned mediating relationship were stronger for employees who perceived themselves as insiders than outsiders. These findings provide theoretical implications for research on UPFB and LSSB and offer some suggestions that managers can follow to inhibit UPFB. Limitations and future research directions are also discussed.